Uniqueness, reciprocity theorems and plane wave propagation in different theories of thermoelasticy - Kumar, Rajneesh; Gupta, Vandana (Zielona Góra: Uniwersytet Zielonogórski)
In this work, a compact form of different theories of thermoelasticity is considered. The governing equations for particle motion in a homogeneous isotropic thermoelastic medium are presented. Uniqueness and reciprocity theorems are proved. The plane wave propagation in a homogeneous isotropic thermoelastic medium is studied. For a three dimensional problem there exist four waves, namely a P-wave, two transverse waves (S1, S2) and a thermal wave (T). From the obtained results the different characteristics of waves such as the phase velocity and attenuation coefficient are computed numerically and presented graphically. Some special cases are also discussed.
Keywords: isotropic; thermoelasticity; uniqueness theorem; reciprocity theorem; plane waves